Preparation method and application of bimetallic MOF-anchored Pt nanocluster catalyst

By loading Pt nanoclusters on the MOF support, forming a bimetallic MOF-anchored Pt nanocluster catalyst, the high energy consumption and stability of the electrocatalyst is solved, and efficient electrochemical water cracking and urea degradation is achieved, providing a Simple and low-cost catalyst preparation method.

CN115770621BActive Publication Date: 2024-12-31YUNNAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211471457.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2024-12-31
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

Existing electrocatalysts have problems of high energy consumption, low efficiency and poor stability in electrochemical water cracking. In particular, the high cost and low abundance of platinum-based catalysts limit their large-scale application, and the conductivity and stability of traditional MOF materials. Not enough to be used directly in HER and UOR.

Method used

The trace Pt nanoclusters were loaded on the metal organic frame (MOF) carrier by room temperature wet chemical etching method to form a bimetallic MOF-anchored Pt nanocluster catalyst. NiMn-MOF was used as a precursor and through hydrothermal reaction and chlorine PtNC/NiMn-MOF composite nanomaterials were prepared by platinum acid solution treatment.

Benefits of technology

Improve the electrocatalytic activity and stability of the catalyst, reduce the overall energy consumption of the electrolytic cell, and achieve efficient HER and UOR catalysis. The nanomaterials show excellent performance under high current density and reach 96.1 in urea degradation. % degradation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115770621B_ABST
    Figure CN115770621B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a bimetallic MOF-anchored Pt nanocluster catalyst, wherein the catalyst is Pt NC / NiMn‑MOF nanomaterial, the catalyst is Pt NC / NiMn‑MOF nanomaterial, which presents a monoclinic nickel-based metal organic framework (Ni‑MOF) structure in its X-ray diffraction spectrum, and the corresponding XRD diffraction angle 2θ ranges from 5° to 50°, wherein the obvious XRD diffraction peaks at 2θ angles of 8.9°, 15.5°, 28.3° and 30.6° correspond to the (200), (400), (20‑2) and (311) crystal planes in the NiMn‑MOF structure, respectively. NC / NiMn‑MOF composite nanomaterials can not only fully decompose urea to produce hydrogen for industrial applications, but also meet the needs of urea wastewater treatment in multiple occasions such as industry and life, realizing wastewater resource utilization and maximizing energy utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-electrocatalytic materials, and in particular to a preparation method and application of a bimetallic MOF-anchored Pt nanocluster catalyst. Background Art

[0002] The increasing energy crisis and environmental pollution force us to explore sustainable alternative energy sources. Hydrogen energy has the advantages of high combustion calorific value, high energy density and pollution-free products, making it one of the cleanest energy sources with the greatest development potential. Green and sustainable electrochemical water splitting to produce hydrogen is an ideal way to mass produce high-purity H2, and the corresponding electrocatalytic hydrogen evolution reaction (HER) has received widespread attention. Generally speaking, the efficiency of electrochemical water splitting to produce hydrogen depends on the catalytic activity and stability of the HER catalyst. Efficient HER electrocatalysts need to accelerate the slow reaction kinetics and reduce the electrode overpotential. At present, commercial Pt / C is still the main hydrogen production catalyst. However, the low abundance and high cost of platinum undoubtedly hinder its large-scale application. To this end, it has become increasingly urgent to develop efficient, stable and more cost-effective hydrogen production electrocatalysts.

[0003] At the same time, the complex four-electron process of the anodic oxygen evolution reaction (OER) in electrochemical water splitting leads to a large driving voltage (usually ≥1.8 V), low energy efficiency and high hydrogen production cost. Therefore, replacing OER with other anodic oxidation reactions with lower thermodynamic voltage will make energy-saving hydrogen production possible. Among the many anodic oxidation reactions, urea oxidation reaction (UOR, CO(NH2)2+6OH - →N2+CO2+5H2O+6e - ) Due to its inherently lower thermodynamic equilibrium potential (0.37 V, relative to the reversible hydrogen electrode (RHE)), the overall potential of UOR is significantly lower than that of OER, thus attracting extensive research interest. Coupling UOR with HER (HER(−)‖UOR(+)) for overall urea electrolysis can not only achieve low-energy hydrogen production, but also purify urea-rich wastewater, thus showing great potential for practical applications.

[0004] In addition, most non-precious metal-based electrocatalysts exist in powder form, so binders are needed to load them onto working electrodes such as glassy carbon and bisulfite plates. The manufacturing process is cumbersome, and most binder materials such as Nafion and polyvinylidene fluoride are expensive, which greatly limits their large-scale application. The use of binders will not only reduce the number of exposed active centers of the catalyst, but also reduce the overall conductivity of the product electrode. In addition, the degree of composite between the binder and the electrocatalyst cannot counteract the stress generated during high current density operation of large catalysts, which greatly reduces the stability of the catalyst. An effective strategy to solve the above problems is to in situ grow-conductive three-dimensional porous skeleton composite nanocatalysts.

[0005] Metal-organic frameworks (MOFs), as an emerging three-dimensional porous composite nanostructure composed of metal nodes and organic ligands, are considered to be a class of catalytic electrode materials with great application prospects. On the one hand, MOFs have abundant and evenly dispersed catalytic metal nodes, which give them a large number of active sites. On the other hand, as porous solid materials, MOFs can be used for both heterogeneous and homogeneous catalysis and can be recycled and reused after the catalytic reaction. However, for most MOF materials, poor intrinsic performance, relatively low conductivity and poor stability are key issues. In situ growth of electrocatalysts onto the surface of NF skeletons can ensure close contact between electrocatalysts and substrates to facilitate charge transfer at the electrocatalyst / substrate interface, and the mechanical stability of the corresponding catalytic electrode can also be greatly improved. Considering the poor conductivity and stability of MOFs, they are rarely used directly as HER and UOR electrocatalysts. Instead, they are usually used as metal carbon-based composite catalysts after high-temperature heat treatment to become catalytically active species. However, heat treatment may damage the advantages of MOF's ordered porous structure, resulting in the aggregation of metal centers and the loss of active centers. Based on this, catalyst loading of MOFs on porous conductive substrates, such as in situ growth of MOFs on NFs, is considered to be an effective approach to overcome the above-mentioned low conductivity and low mass permeability.

[0006] In order to further improve the conductivity and catalytic activity of MOF-based catalytic electrode materials, it is considered an effective way to modify trace amounts of precious metals onto the surface of MOF structures. Further reducing the size of the modified precious metals to the scale of nanoclusters is bound to greatly improve the catalytic activity and stability of the composite catalyst. This is because the nanocluster catalyst composed of several atoms has a high atomic utilization rate and has a unique electronic structure and geometric configuration. It can maximize the material conversion and accelerate the reaction rate during the catalytic reaction. Although various precious metal nanoclusters have been reported in the past few years and play an important role in the field of electrocatalysis. However, due to the large surface energy of cluster atoms, metal atoms are very easy to migrate and aggregate, resulting in reduced catalytic activity. Therefore, how to stabilize the metal atoms of nanoclusters on a certain carrier is the key to preparing highly active nanoclusters. Although many synthetic methods, such as chemical vapor deposition, high-temperature pyrolysis, atomic layer deposition and microwave heating, have been proven to stabilize nanoclusters, most of the synthetic routes are complicated and require high temperature or high pressure conditions. Therefore, developing and designing a general strategy that is easy to prepare and low-cost to achieve the anchoring of Pt nanoclusters by metal-organic framework nanomaterials is a technical challenge that needs to be urgently solved by technicians in this field. Summary of the invention

[0007] To this end, the main purpose of the present invention is to provide a preparation method and use of a bimetallic MOF-anchored Pt nanocluster catalyst to solve the problems existing in the background technology.

[0008] It should be noted that the metal organic framework (MOF) precursor prepared by this method is a catalytic material with broad application prospects. It is constructed by metal ions / clusters and organic linkers, can provide a clear structure and a clear active center, and is easy to regulate the electronic structure of the metal site; and the MOF precursor has a rich pore structure and a large specific surface area, which is easy to contact with the electrolyte, which is conducive to accelerating the mass transfer process and effectively reducing the overall energy consumption of the (HER(−)‖UOR(+) electrolytic cell. Loading Pt nanoclusters on the MOF carrier by room temperature wet chemical etching can not only improve the utilization rate of Pt and increase the electrocatalytic activity of composite nanomaterials, but also provide a new synthetic idea for the research of materials for industrial applications.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0010] A bimetallic MOF-anchored Pt nanocluster catalyst, wherein the catalyst is Pt NC / NiMn-MOF nanomaterial, which presents a monoclinic nickel-based metal-organic framework (Ni-MOF) structure in its X-ray diffraction spectrum, and the corresponding XRD diffraction angle 2θ ranges from 5° to 50°, among which the obvious XRD diffraction peaks appearing at 2θ angles of 8.9°, 15.5°, 28.3° and 30.6° correspond to the (200), (400), (20-2) and (311) crystal planes in the NiMn-MOF structure, respectively.

[0011] The present invention also provides a method for preparing a bimetallic MOF-anchored Pt nanocluster catalyst, wherein the catalyst is Pt NC / NiMn-MOF, the method comprises: using metal nickel and manganese as metal nodes, using terephthalic acid as an organic ligand to in-situ grow a NiMn-MOF precursor on nickel foam, and then using a room temperature wet chemical etching method to load Pt nanoclusters onto the surface of the NiMn-MOF precursor to obtain Pt NC / NiMn-MOF composite nanomaterials.

[0012] Furthermore, the preparation method comprises the following steps:

[0013] Step (1): pretreatment of nickel foam;

[0014] Step (2): Add metal nickel salt, metal manganese salt and terephthalic acid to a solvent.

[0015] The reagent is composed of ethanol, N,N-dimethylformamide and deionized water, and is stirred evenly to obtain an initial mixed solution;

[0016] Step (3): transferring the initial mixed solution and nickel foam to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction. Preferably, the reaction temperature of the hydrothermal reaction is 120°C to 160°C, and the reaction time is 12 h to 24 h.

[0017] Step (4): taking out the nickel foam after the reaction, washing it with alcohol, and drying it at room temperature to obtain

[0018] Bimetallic organic framework NiMn-MOF precursor;

[0019] Step (5): Immerse the obtained NiMn-MOF precursor in a certain amount of chloroplatinic acid solution at room temperature.

[0020] The reaction was carried out in a dark environment for 1 h, and then the nickel foam was washed with alcohol and vacuum dried to obtain Pt NC / NiMn-MOF nanomaterial, preferably, the concentration of the chloroplatinic acid solution is 1 mg / mL~3 mg / mL.

[0021] Pt NC / NiMn-MOF is a NiMn-MOF nanomaterial with regular nanosheet morphology formed by Ni and Mn as metal sites and p-dibenzoic acid as organic ligand. A simple low Pt concentration room temperature wet chemical etching method is used to prepare highly active Pt NC / NiMn-MOF composite nanomaterials.

[0022] The method for preparing the nanocluster / MOF composite structure disclosed in the present invention is simple, has low energy consumption, and is suitable for industrial production. A synthetic dual-function MOF-anchored Pt nanocluster catalyst prepared by the method of the present invention can be used as a catalyst for high-current HER, UOR and urea degradation applications, which not only overcomes the problem that traditional catalysts have a single function, but also has better performance than commercial Pt / C in high-current HER. At the same time, the method for preparing nanoclusters is simple, which provides a new idea for the synthesis of highly active nanocluster catalysts.

[0023] In the one-step method for synthesizing bimetallic organic framework nanomaterials, in step (2), the metal nickel salt is nickel nitrate [Ni(NO3)2 or Ni(NO3)2·6H2O], nickel sulfate [NiSO4, NiSO4·H2O, NiSO4·2H2O, NiSO4·4H2O, NiSO4·6H2O or NiSO4·7H2O] or nickel chloride [NiCl2, NiCl2·6H2O]; the metal manganese salt is manganese nitrate [Mn(NO3)2∙4H2O or Mn(NO3)2∙2H2O], manganese sulfate [MnSO4∙7H2O, MnSO4·H2O or MnSO4·4H2O] or manganese chloride [MnCl2, MnCl2∙4H2O]; and the solvent is composed of N,N-dimethylformamide, ethanol and deionized water.

[0024] Preferably, in step (2), the molar ratio of the metal nickel salt, the metal manganese salt and terephthalic acid is (0.1-1.0):(0.1-1.0):(0.1-1.0).

[0025] Preferably, in step (2), the volume ratio of the solvent N,N-dimethylformamide, ethanol and deionized water is 4:3:1.

[0026] Preferably, the drying temperature in step (5) is 60 °C and the drying time is 8 h.

[0027] The present invention also claims a bimetallic MOF anchored Pt nanocluster catalyst prepared by the above method, wherein the nanocluster synthesis method is to use a nanomaterial with a nanosheet structure formed by a metal organic framework as a precursor, and to synthesize Pt under etching with a chloroplatinic acid aqueous solution at room temperature. NC / NiMn-MOF composite nanomaterial; this material can be used as an electrocatalyst in high-current HER, urea electrocatalysis and electrocatalytic urea degradation to improve the catalytic efficiency.

[0028] The technical solution of the present invention achieves the following beneficial technical effects:

[0029] The present invention provides a novel bimetallic MOF-anchored Pt nanocluster catalyst, which has excellent performance and wide application.

[0030] The bimetallic MOF-anchored Pt nanocluster catalytic electrode nanomaterial synthesized by the present invention first uses Ni and Mn as metal nodes and p-dibenzoic acid as an organic ligand to prepare a NiMn-MOF nanomaterial precursor; then the Pt nanocluster is loaded onto the MOF precursor by a room temperature wet chemical etching method. The present invention overcomes the shortcomings of the complex synthesis path of the nanocluster synthesized by other existing technologies, and also overcomes the problems of the instability and single function of conventional MOF powder electrodes.

[0031] The Pt prepared by the present invention NC / NiMn-MOF composite nanomaterials only require overpotentials of 56 mV, 170 mV, and 289 mV, respectively, to reach 100 mA·cm in the electrocatalytic hydrogen evolution process. -2 , 500 mA·cm -2 and 1000 mA·cm -2 The current density of 1.0 mol / L KOH + 0.33 mol / L Urea can provide a new idea for the preparation of industrial hydrogen production materials. At the same time, the nanomaterial can quickly and efficiently degrade urea in urea wastewater into N2 and CO2, and the corresponding urea degradation rate (electrolyte is 1.0 mol / L KOH + 0.33 mol / L Urea) can reach 96.1% in a short time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the synthesis of a bimetallic MOF-anchored Pt nanocluster catalyst in an embodiment of the present invention;

[0033] Figure 2 XRD spectrum of a bimetallic MOF anchored Pt nanocluster catalyst (NiMn-MOF and Pt NC / NiMn-MOF);

[0034] Figure 3 A scanning electron microscope image of a bimetallic NiMn-MOF catalyst nanomaterial prepared in an embodiment of the present invention, wherein a is a SEM image and b is an EDS spectrum of the material components;

[0035] Figure 4 Scanning electron microscope image of a bimetallic MOF-anchored Pt nanocluster catalyst nanomaterial prepared in an embodiment of the present invention, where a is Pt NC a is the SEM image of / NiMn-MOF, b is the EDS spectrum.

[0036] Figure 5 A scanning transmission electron microscope (TEM) image of a bimetallic MOF-anchored Pt nanocluster catalyst prepared in an embodiment of the present invention, wherein a and b are Pt NC TEM image of / NiMn-MOF and the enlarged image of the corresponding position;

[0037] Figure 6 HER performance diagram of a bimetallic MOF-anchored Pt nanocluster catalyst prepared in an embodiment of the present invention and its comparative sample under high current conditions, where a is the LSV polarization curve and b is the corresponding performance histogram. ;

[0038] Figure 7UOR performance diagram of a bimetallic MOF catalyst prepared in an embodiment of the present invention and its comparative sample, where a is Pt NC a is the UOR polarization curve (LSV) of / NiMn-MOF and its comparative sample, b is the performance comparison of the samples at different current densities.

[0039] Figure 8 HER and UOR stability test diagram of a bimetallic MOF-anchored Pt nanocluster catalyst prepared in an embodiment of the present invention, where a is Pt NC LSV performance comparison of NiMn-MOF after 1000 CV cycles in the HER process, b is Pt NC / Comparison of LSV performance of NiMn-MOF after 1000 CV cycles in UOR process;

[0040] Fig. 9 Urea degradation performance diagram of Ni-MOF and NiMn-MOF catalysts prepared in the examples of the present invention, wherein a is the urea degradation performance diagram of Ni-MOF, and b is the urea degradation performance diagram of NiMn-MOF;

[0041] Fig.10 The Pt prepared in the embodiment of the present invention NC / NiMn-MOF catalyst urea degradation performance diagram, where a is the urea degradation performance diagram of Pt / NiMn-MOF, b is the urea degradation performance diagram of Pt NC / Comparison of urea degradation performance of NiMn-MOF, NiMn-MOF, and Ni-MOF catalysts. DETAILED DESCRIPTION

[0042] The advantages and characteristics of the present disclosure, and methods for achieving the same, will become apparent with reference to the following embodiments in conjunction with the accompanying drawings. However, the embodiments should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art.

[0043] If not otherwise defined, all terms (including technical and scientific terms) in this specification may be defined as commonly understood by those skilled in the art to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the present disclosure and the relevant art, and will be interpreted in a non-idealized or overly formal sense unless clearly defined herein.

[0044] The chemical reagents used in the present invention, unless otherwise specified, were of analytical grade and purchased from the market, and the concentration of ethanol used was 99.99%.

[0045] The present invention provides a bimetallic MOF anchored Pt nanocluster catalyst, such as Figure 2 As shown, the catalyst is Pt NC / NiMn-MOF nanomaterial, which presents a monoclinic nickel-based metal-organic framework (Ni-MOF) structure in its X-ray diffraction spectrum, and the corresponding XRD diffraction angle 2θ ranges from 5° to 50°, among which the obvious XRD diffraction peaks appearing at 2θ angles of 8.9°, 15.5°, 28.3° and 30.6° correspond to the (200), (400), (20-2) and (311) crystal planes in the NiMn-MOF structure, respectively.

[0046] Example 1

[0047] A simple two-step synthesis of a bimetallic MOF-anchored Pt nanocluster catalyst Figure 1 As shown, the specific steps include:

[0048] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0049] Step (2): add 1 mmol of metal nickel salt Ni(NO3)2·6H2O, 0.8 mmol of metal manganese salt Mn(NO3)2·4H2O and 1 mmol of p-dibenzoic acid C8H6O4 to a solvent consisting of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stir evenly to form an initial mixed solution;

[0050] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 120 °C for 12 h;

[0051] Step (4): washing the nickel foam with alcohol and vacuum drying to obtain the NiMn-MOF precursor.

[0052] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 1 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., Pt NC / NiMn-MOF.

[0053] The drying temperature of the vacuum drying in step (4) and step (5) is 60 °C and the drying time is 8 h.

[0054] This embodiment uses a simple hydrothermal and room temperature wet chemical etching method to synthesize a bimetallic MOF-anchored Pt nanocluster catalyst in two steps, which provides a synthetic reference for MOF structure-anchored nanoclusters; the synthesized material has HER and UOR dual functional properties, and can be used in industrial high-current water electrolysis to produce hydrogen; the application for urea oxidation is mainly urea degradation testing.

[0055] Figure 1 A simple schematic diagram of the synthesis of MOF-anchored Pt nanoclusters. Pt was synthesized by a two-step synthesis method using simple hydrothermal and room temperature wet chemical etching. NC / NiMn-MOF nanocomposites.

[0056] Figure 2 The NiMn-MOF and Pt prepared in this example NC From the XRD of NiMn-MOF, we can see that except for the X-ray diffraction peak of NiMn-MOF, there is no X-ray diffraction peak of metal Pt, which can be inferred that Pt is not loaded on NiMn-MOF in the form of nanoparticles. Figure 3 It can be seen that the main chemical components of NiMn-MOF are nickel, manganese, carbon and oxygen, and its corresponding microscopic nanomorphology is a self-supporting two-dimensional porous nanosheet structure. Figure 4 The Pt prepared in this example NC From the scanning electron microscope image of the NiMn-MOF nanomaterial, it was found that its main chemical components are platinum, nickel, manganese, carbon and oxygen, and the loading of Pt did not change the micromorphology of the NiMn-MOF precursor. It can be inferred that the Pt in the MOF precursor may exist in the form of nanocluster doping. Figure 5 The Pt prepared in this example NC Dark field scanning transmission electron microscope (HAADF-STEM) photo of NiMn-MOF nanomaterial. Generally, the brightness of each metal atom in the HAADF mode is proportional to the 1.8th power of the corresponding atomic number. The Pt atom has the largest atomic number in this system, so the Pt atom is brighter than the Ni, Mn, O and other substrate atoms in NiMn-MOF. Therefore, Figure 5 The bright spots marked with circles in b are Pt clusters, that is, Pt exists in the catalyst in the form of nanoclusters.

[0057] Example 2

[0058] A simple two-step synthesis of a bimetallic MOF-anchored Pt nanocluster catalyst Figure 1 As shown, the specific steps include:

[0059] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0060] Step (2): add 1 mmol of metal nickel salt Ni(NO3)2·6H2O, 0.8 mmol of metal manganese salt Mn(NO3)2·4H2O and 1 mmol of p-dibenzoic acid C8H6O4 to a solvent, wherein the solvent is composed of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stir evenly to form an initial mixed solution;

[0061] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 140 °C for 12 h;

[0062] Step (4): washing the nickel foam with alcohol and vacuum drying to obtain the NiMn-MOF precursor.

[0063] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 2 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., Pt NC / NiMn-MOF.

[0064] In step (4) and step (5), the drying temperature is 60 °C and the drying time is 8 h.

[0065] Example 3

[0066] A simple two-step synthesis of a bimetallic MOF-anchored Pt nanocluster catalyst Figure 1 As shown, the specific steps include:

[0067] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0068] Step (2): add 1 mmol of metal nickel salt Ni(NO3)2·6H2O, 0.8 mmol of metal manganese salt Mn(NO3)2·4H2O and 1 mmol of p-dibenzoic acid C8H6O4 to a solvent consisting of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stir evenly to form an initial mixed solution;

[0069] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 160 °C for 12 h;

[0070] Step (4): washing and drying the nickel foam to obtain the NiMn-MOF precursor.

[0071] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 3 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., Pt NC / NiMn-MOF.

[0072] In step (4) and step (5), the drying temperature is 60 °C and the drying time is 8 h.

[0073] Example 4

[0074] A method for preparing a bimetallic MOF-anchored Pt nanocluster catalyst comprises the following steps:

[0075] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0076] Step (2): add 1 mmol of metal nickel salt Ni(NO3)2·6H2O, 0.8 mmol of metal manganese salt Mn(NO3)2·4H2O and 1 mmol of p-dibenzoic acid C8H6O4 to a solvent consisting of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stir to form an initial mixed solution;

[0077] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 120 °C for 12 h;

[0078] Step (4): washing the nickel foam with alcohol and vacuum drying (drying temperature is 60 ° C, drying time is 8 h) to obtain the NiMn-MOF precursor.

[0079] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 2 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried (drying temperature is 60 ° C, drying time is 8 h) to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., PtNC / NiMn-MOF.

[0080] Example 5

[0081] A method for preparing a bimetallic MOF-anchored Pt nanocluster catalyst comprises the following steps:

[0082] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0083] Step (2): 1 mmol of metal nickel salt NiCl2·6H2O, 0.8 mmol of metal manganese salt MnCl2∙4H2O and 1 mmol of p-dibenzoic acid C8H6O4 are added to a solvent consisting of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stirred to form an initial mixed solution;

[0084] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 120 °C for 24 h;

[0085] Step (4): washing the nickel foam with alcohol and vacuum drying to obtain the NiMn-MOF precursor.

[0086] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 1 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., Pt NC / NiMn-MOF.

[0087] The drying temperature of the vacuum drying in step (4) and step (5) is 60 °C and the drying time is 8 h.

[0088] Example 6

[0089] A method for preparing a bimetallic MOF-anchored Pt nanocluster catalyst comprises the following steps:

[0090] Step (1): Pre-treat the nickel foam NF by ultrasonicating it in 3 M hydrochloric acid for 15 minutes, then ultrasonicating it in ultrapure water for 10 minutes, and finally ultrasonicating it in ethanol for 5 minutes, and then air-dry it for later use;

[0091] Step (2): 1 mmol of metal nickel salt NiSO4·6H2O, 0.8 mmol of metal manganese salt MnSO4·4H2O and 1 mmol of para-dibenzoic acid C8H6O4 are added to a solvent consisting of 15 mL of ethanol, 20 mL of N,N-dimethylformamide and 5 mL of deionized water, and stirred to form an initial mixed solution;

[0092] Step (3): transferring the initial mixed solution and nickel foam into a 100 ml polytetrafluoroethylene reactor and reacting at 120 °C for 24;

[0093] Step (4): washing the nickel foam with alcohol and vacuum drying to obtain the NiMn-MOF precursor.

[0094] Step (5): The obtained NiMn-MOF precursor is placed in 10 mL of 3 mg / mL chloroplatinic acid solution and reacted in a dark environment at room temperature for 1 h. The nickel foam after the reaction is then washed with alcohol and vacuum dried to obtain the bimetallic NiMn-MOF anchored Pt nanocluster catalytic nanomaterial, i.e., Pt NC / NiMn-MOF.

[0095] The drying temperature of the vacuum drying in step (4) and step (5) is 60 °C and the drying time is 8 h.

[0096] The bifunctional Pt prepared in Example 1 of the present invention NC The HER catalytic activity and UOR catalytic activity of the / NiMn-MOF composite nanomaterials were tested respectively, and they were used for urea degradation to test their urea degradation performance.

[0097] (1) Testing the HER catalytic activity of the prepared catalyst using a three-electrode system

[0098] Take the Pt prepared in Example NC / NiMn-MOF (cut into 1 cm×1 cm size) was used as the working electrode, Pt electrode was used as the auxiliary electrode (if the current is too large, the carbon rod will corrode and fall off), Hg / HgO electrode was used as the reference electrode, and 1 mol / L KOH (100mL) was prepared as the electrolyte to test the HER catalytic performance under high current conditions.

[0099] from Figure 6 a It can be seen that the Pt prepared in Example NC / NiMn-MOF as HER catalyst, driving 100 mA·cm -2 The overpotential of the current density is only 56 mV. Figure 6 As can be seen from b, Pt NCThe HER catalytic activity of NiMn-MOF at high current density is comparable to or even better than that of commercial Pt / C, which provides a new research idea for the expansion of HER hydrogen production material systems for industrial applications. Considering that the introduction of Pt clusters greatly improves the HER catalytic activity of NiMn-MOF, it is indirectly proved that Pt clusters are the main active species of HER. In addition, the HER catalytic performance of Ni-MOF and NiMn-MOF is similar, which to a certain extent reflects that Ni and Mn sites are not the real active sites of HER, and they mainly play a synergistic role as carriers. In addition, from Figure 8 aIt can be seen that Pt NC After 10,000 CV cycles in the HER process, the LSV performance of NiMn-MOF did not change much, indicating that it has good stability, further proving that Pt NC / NiMn-MOF has great potential in the field of industrial water electrolysis to produce hydrogen.

[0100] Figure 6 to Figure 7 In the figure, nickel foam (NF): 1 cm × 1 cm, purchased from Cyber ​​Materials Network; ruthenium dioxide (RuO2): McLean; Ni-MOF and NiMn-MOF- are precursors prepared by the method of this embodiment under the synthesis conditions of 120 °C and 12 h, the difference between which is the type and proportion of the added metal source. Pt NC / NiMn-MOF is a Pt single atom-loaded MOF nanomaterial prepared by room temperature wet chemical etching method using NiMn-MOF as a precursor.

[0101] (2) Testing the UOR catalytic activity of the prepared catalyst using a three-electrode system

[0102] Take the Pt prepared in Example NC / NiMn-MOF (cut into 1 cm×1 cm size) was used as the working electrode, graphite carbon rod and Hg / HgO electrode were used as the auxiliary electrode and reference electrode respectively, and 100 mL 1 mol / L KOH + 0.33 mol / L urea was prepared as the electrolyte to test the electrocatalytic urea oxidation performance.

[0103] from Figure 7 a and Figure 7 b It can be seen that Pt NC The UOR catalytic performance of / NiMn-MOF is the best at 200 mA·cm -2 and 300 mA·cm -2 The driving voltages of UOR at the current density were 1.34 V and 1.35 V, respectively, which are much lower than those of NiMn-MOF, Ni-MOF and commercial RuO2 catalysts. Figure 7From the LSV polarization curve in a, it can be seen that Mn doping can greatly improve the UOR catalytic performance of Ni-based two-dimensional MOF, which may be attributed to the high-valent Mn doping regulating the electronic structure of Ni-MOF and optimizing its adsorption and desorption of intermediates in the urea oxidation process. In addition, the introduction of Pt clusters can further synergize with NiMn-MOF to increase the conductivity and catalytic activity of the MOF carrier. Figure 8 b It can be seen that Pt NC The LSV polarization curve of / NiMn-MOF in the UOR process did not change much after 1000 CV cycles, proving its good urea oxidation stability. As we all know, the stability of MOF material system has always been a core issue in the field of catalysis, whether it is basic research or industrial application. In this case, the catalytic activity and stability of Ni-based two-dimensional MOF were greatly improved by nanocluster modification and atomic doping, which provides new insights into the development, design and application of MOF-based materials.

[0104] (3) Urea degradation performance of the prepared catalyst tested by two electrodes

[0105] Urea degradation was tested using two-electrode electrodegradation, where both the cathode and anode were made of self-supporting Pt NC / NiMn-MOF, or NiMn-MOF or Ni-MOF nanomaterials (4 cm×4 cm) were prepared, and then 100 mL of 1 mol / L KOH + 0.33 mol / L urea solution was prepared as the electrolyte. The urea degradation performance was tested and compared with this system.

[0106] Fig. 9 ab and Fig.10 ab are the performance diagrams of urea degradation test. Fig. 9 ab and Fig.10 As can be seen from ab, the bifunctional Pt prepared in Example NC / NiMn-MOF composite nanomaterials were used as catalytic electrodes to electrocatalyze the degradation of urea-rich alkaline electrolyte. After three hours of degradation, the urea degradation rate in the system could reach 96.1%, and its urea degradation performance was much better than that of NiMn-MOF and Ni-MOF, indicating that Pt NC / NiMn-MOF has good degradation performance for urea, which provides a new strategy for the treatment of urea-rich wastewater in daily life.

[0107] In summary, the above embodiments are merely examples for clearly illustrating the applications, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A bimetallic MOF-anchored Pt nanocluster catalyst for use in water electrolysis to produce hydrogen or urea degradation, characterized in that: The preparation method of the bimetallic MOF anchored Pt nanocluster catalyst comprises the following steps: Step (1): pretreatment of nickel foam; Step (2): adding a metal nickel salt, a metal manganese salt and terephthalic acid to a solvent, wherein the solvent is composed of ethanol, N,N-dimethylformamide and deionized water, and stirring to obtain an initial mixed solution; Step (3): transferring the initial mixed solution and nickel foam to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction, wherein the reaction temperature of the hydrothermal reaction is 120° C. to 160° C. and the reaction time is 12 h to 24 h; Step (4): taking out the nickel foam after the reaction, washing it with alcohol, and vacuum drying it to obtain a bimetallic organic framework NiMn-MOF precursor; Step (5): Immerse the obtained NiMn-MOF precursor in a certain amount of chloroplatinic acid solution and react it in a dark environment at room temperature for 1 hour. Then, wash the nickel foam after the reaction with alcohol and vacuum dry it to obtain Pt NC / NiMn-MOF nanomaterials, the concentration of chloroplatinic acid solution is 1 mg / mL~3 mg / mL.

2. The use according to claim 1, characterized in that In step (1), the pretreatment method is: first immerse the nickel foam of 2 cm×3 cm in 3 mol / L hydrochloric acid for 15 minutes, then immerse it in ultrapure water for 10 minutes, and finally immerse it in ethanol for 5 minutes, and then air-dry it for later use.

3. The use according to claim 1, characterized in that The metal nickel salt in step (2) is one of nickel nitrate, nickel sulfate and nickel chloride, and the metal manganese salt is one of manganese nitrate, manganese sulfate and manganese chloride.

4. The use according to claim 1, characterized in that In step (2), the molar ratio of metal nickel salt, metal manganese salt and terephthalic acid in the MOF precursor synthesis is (0.1~1.0):(0.1~1.0):(0.1~1.0).

5. The use according to claim 1, characterized in that: In step (2), the volume ratio of the solvent N,N-dimethylformamide, ethanol and deionized water is 4:3:

1.

6. The use according to claim 1, characterized in that: The drying temperature of the vacuum drying in step (4) and step (5) is 60°C and the drying time is 8 h.

Citation Information

Patent Citations

  • High activity electric catalyst using metal organic skeleton as carrier and preparation method thereof

    CN103219531A

  • Monatomic catalyst prepared based on surface immobilizing method

    CN111013576A

  • Method for preparing superfine cerium dioxide supported metal monatomic catalyst from cluster-based framework material

    CN114293223A

  • Preparation method of Pt nano-particle modified bimetallic LDH catalyst and application of Pt nano-particle modified bimetallic LDH catalyst in industrial current density electrolysis of water

    CN117089881A

  • Method for producing hydrogen molecules by means of energy radiation

    WO2022121574A1